Coupled computational fluid dynamics-population balance model approach for investigating effect of breakage, coalescence, and interfacial forces in continuous emulsification using static mixers - Salunkhe, Neha Sudhakar; Dastane, Gaurav; Mali, Chaitanya R. (Industrial & Engineering Chemistry Research, 2026)
This study employs a coupled CFD-PBM framework to investigate the effects of breakage and coalescence kernels as well as interfacial force models on droplet dynamics in turbulent liquid-liquid dispersions. An Euler-Euler two-phase model integrated with the population balance model was used to evaluate the influence of turbulence models and breakup-coalescence kernels on droplet formation. The role of interfacial forces, including drag, lift, and turbulent dispersion, was systematically assessed with respect to interfacial area concentration, dispersed phase volume fraction variation, turbulent dissipation rate, Sauter mean diameter (d 32), and droplet size distribution. Through sensitivity analysis, an optimized CFD-PBM model was developed, capable of accurately predicting droplet dynamics. The predicted d 32 showed excellent agreement with the measured experimental data, with a deviation of approximately 0.2% relative to the reported values. Incorporating the lift force improved the prediction of dispersed phase volume fraction by approximately 6.06%, while the inclusion of the turbulent dispersion force enhanced the phase redistribution and increased the local turbulent dissipation rate in the initial mixing zone by nearly 4.68%, thereby promoting droplet breakage. Furthermore, spectral analysis of velocity time-series data using the fast Fourier transform revealed a -5/3 slope in the energy spectrum, confirming that the simulations captured the inertial subrange of turbulence.